Willingness-to-pay for energy-saving retrofits of residential buildings and its influencing factors: the case of the Pearl River Delta, China - Hongyang, Li; Shuying, Fang; Skitmore, Martin; Talebian, Nima (Technological and Economic Development of Economy, 2022)
In the 21st Century, the construction industry regards green building as an important breakthrough to achieve sustainable development, and energy-saving retrofits of residential buildings has been conducted globally with China no exception. In order to better understand consumers’ attitudes and willingness-to-pay (WTP) for green retrofits and identify the shortcomings of the industry’s development, this study designs a retrofit scheme and organizes a questionnaire survey to collect feedback of responds from the Pearl River Delta, China regarding their WTP for energy-saving retrofits of residential buildings and their decision factors. The study identifies a retrofit cost of 517.92 and found that 94.29% of respondents had the intention of green reconstruction. The results of a Pearson correlation analysis and one-way ANOVA show the professional background of respondents and their WTP to be negatively correlated, while education level, perceived value, perceived behavior control, and feelings of the surrounding reference group are positively correlated with participants’ expected inputs. Of all the factors considered, the level of education and feelings of the surrounding reference group influence budget most significantly. The findings will help property developers and the government to design better marketing strategies and launch corresponding policies, thereby promoting the development of the green building industry. First published online 29 September 2022